Corrigendum - Agrivita, Agrivita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Corrigendum to “Nutritional and Agronomical Performance of Five Rice Varieties Cultivated in Saline Soils Amended with Leonardite” [AGRIVITA Journal of Agricultural Science, 45(3), 589-599]